Simulation of Organic Rankine Cycle - quasi-steady state vs dynamic approach for optimal economic performance - Pili, Roberto (2020)
Computer-based simulations of Organic Rankine Cycles (ORC) have been extensively used in the last two decades to predict the behaviour of existing plants or already in the design phase. For time-varying heat sources, researchers typically rely on either quasi-steady state or dynamic simulations. In this work, the two approaches are compared and the trade-off between them is analysed, taking as benchmark waste heat recovery with ORC from a billet reheating furnace. The system is firstly optimized in MATLAB® using a quasi-steady state approach. The results are then compared with a corresponding dynamic simulation in Dymola. In the case of waste heat from billet reheat furnace, the quasi-steady state approach can successfully capture the fluctuations in waste heat. For heat source ramps from 110% to 40% the nominal value in 30 s, dynamic effects lead to 1.1% discrepancies in ORC net power. The results highlight the validity of the quasi-steady state approach for techno-economic optimization of ORC for industrial waste heat and provide a valuable guideline for developers, companies and researchers when choosing the most suitable tool for their analysis, helping them save time and costs to find the most appropriate approach.